Newton projection with proportioning using iterative linear algebra for model predictive control with long prediction horizon. (3rd September 2019) - Otta, Pavel; Burant, Jiří; Šantin, Ondřej; Havlena, Vladimír
ABSTRACT: This paper presents an algorithm to solve a sparse Quadratic Programming (QP) problem. The QP problem is suitable for Model Predictive Control (MPC) applications in particular. MPC is a modern multivariable control method which requires the solution to a quadratic programming problem at each sampling instant. The proposed algorithm is an active-set based strategy which uses the proportioning test for the selection of the active-set reduction and expansion while utilizing the sparse nature of the problem by the preconditioned MINRES algorithm to solve the face problem. Numerical experiments illustrate the performance of the algorithm, and the results are compared with the state-of-the-art solvers.